Assessment of soil fertility management practices of wheat in western terai of Nepal - Rawal, N.; Bhandari, N.; Subedi, S.; Chalise, D. R.; Khadka, D. (Journal of the Institute of Agriculture and Animal Science, 2018)
A study was conducted to assess the soil fertility management practices and their constraints in sixty households of western terai of Nepal namely Barrohiya (Kapilvastu), Rehara (Rupandehi) and Sanda (Nawalparasi) in 2013 by using simple random sampling techniques. A semi-structured interview schedule was used for the collection of the data. Eighty percent of the interviewed farmers had medium land holding size (7.5 to 82 Katha). Most of the land was irrigated (>81 percent) and medium upland type (53.48 percent). Farmers in those areas weren’t practicing green manuring but were habituated to incorporate legumes (pea, lentil, black gram, beans, etc.). Chemical fertilizer was the main source of nutrient (56 percent) for wheat crop. Urea and DAP were commonly used by farmers whereas MoP was rarely used. Farmers of Kapilvastu applied the highest amount of Urea (165 Kg/ha) where as the amount of DAP (116.9 kg/ha) and MoP (27.8 Kg/ha) used was more in Nawalparasi than other two in wheat crop. On an average the farmers applied 13.3 kg/ha MoP which is very low as compared to recommended dose (41.7 kg/ha). There were number of constraints and obstacles perceived by the farmers. Arrangement must be made on those areas for time availability of fertilizers and farmers must be made aware about adequate use of quality chemical fertilizers and proper soil nutrient management. Journal of the Institute of Agriculture and Animal Science. Vol. 33-34, 2015, page: 105-114